Rancangan Penerjemah Bahasa Inggris - Indonesia Menggunakan Teknik Kecerdasan Buatan - Widodo, Yohanes Bowo (JIK: Jurnal Ilmu Komputer, 2004)
Natural Language processing is a topic intensely discussed in computer science nowdays. The term natural language is used to represent common human language because in computer science there are other classifications of language, such as programming language, formal language, etc. Researches in natural language area have given the computer ability to understand human language (in a certain level) and to translate between one natural language to another natural language. There are many unstructured aspects should be considered so that good rules could be applied by the computer in order to make good translation or understanding. These unstructured aspects could not be solved by mere conventional computer science concepts. There are new concepts in computer science could be used to gain good unstructured problem solving. These concepts are artificial intelligence, fuzzy logic, object oriented, hypertext, and neural networks. The growth of hardware capability also giving good support to the unstructured problems found in natural language. This research is intended to analyze and to apply recent concepts discussed above, to solve natural language processing problems, especially in natural language translation, in this case, English to IndonesianKata Kunci : Language, Strutural Language, Unstruktural language